Ca2+-stimulated adenylyl cyclases as therapeutic targets for psychiatric and neurodevelopmental disorders - Jiao Chen; Qi Ding; Lulu An; Hongbing Wang (Frontiers in Pharmacology, 2022)
As the main secondary messengers, cyclic AMP (cAMP) and Ca2+ trigger intracellular signal transduction cascade and, in turn, regulate many aspects of cellular function in developing and mature neurons. The group I adenylyl cyclase (ADCY, also known as AC) isoforms, including ADCY1, 3, and 8 (also known as AC1, AC3, and AC8), are stimulated by Ca2+ and thus functionally positioned to integrate cAMP and Ca2+ signaling. Emerging lines of evidence have suggested the association of the Ca2+-stimulated ADCYs with bipolar disorder, schizophrenia, major depressive disorder, post-traumatic stress disorder, and autism. In this review, we discuss the molecular and cellular features as well as the physiological functions of ADCY1, 3, and 8. We further discuss the recent therapeutic development to target the Ca2+-stimulated ADCYs for potential treatments of psychiatric and neurodevelopmental disorders.